Effect of Different Wine-Making Techniques on the Composition and Quality of Pinotage Wine. II. Juice/Skin Mixing Practices - Marais, J. (South African Journal of Enology and Viticulture, 2017)
The effect of different juice/skin mixing practices (punching-down of the cap, pumping-over of the juice and the rotor action, and the frequency at which these actions were performed) on Pinotage wine composition and quality, was investigated over three seasons (2000 to 2002). Wines were analysed for total polyphenols (flavonoids, tannins, anthocyanins) and esters, and sensorially evaluated for Pinotage cultivar character (berry/plum) intensity and overall wine quality. The punching-down and rotor treatments yielded the highest, and the pumping-over treatment the lowest total polyphenol concentrations. Although it appeared that the 3-hourly action yielded slightly higher polyphenol concentrations than the 1-hourly action, no statistical differences were observed between the two treatments.  Irrespective of season, the rotor treatment yielded the highest acetate ester concentrations. The corresponding wines reflected the individual treatments to a great extent, and in general the wine qualities of the punching-down and rotor treatments were of the same order, but higher than those of the pumping-over treatment. Wine quality did not differ significantly between the 1- and 3-hourly treatments, irrespective of the mixing technique and season.